洗煤厂多级带传输多触摸屏多CAN板并联远距集控装置 (2018)
本发明专利为洗煤厂多级带传输多触摸屏多CAN板并联远距集控装置，包括洗煤厂多级带式运输监控装置，多个触摸屏和CAN板并联后，通过RS485串口线与PLC串口连接；抱闸检测开关、主接触器的触点反馈检测开关与PLC的输入输出端点连接；各个从机出现通信故障，及时发现。具有抱闸、烟雾、堆煤、打滑、电机温度、前滚筒温度、后滚筒温度、前跑偏、中跑偏、后跑偏的保护功能，并可在触摸屏中进行解除/投入设置；各个触摸屏中显示电流、电压和功率，能够实现具有多触摸屏多CAN板远距监控的功能，适用于多数据的处理，数据传输快，信号衰减小，抗干扰能力强。其功能齐全、性能可靠。 A multistage band transportation multi-touch-screen multi-CAN-board parallel long-distance centralized control device for a coal washery comprises a multistage band-type transportation monitoring device for a coal washery. Multiple touch screens are connected in parallel with the CAN boards, and then are connected to a PLC serial port by means of RS 485 serial port lines. A band-type brake detection switch and a contact feedback detection switch of a main contactor are connected to input/output endpoints of the PLC; in a case in which secondary machines encounter communication faults, the faults can be found in time. The device has protection functions for a band-type brake, smoke, coal stacking, skidding, a motor temperature, a front ro